Pharmacologic management of weight regain following bariatric surgery - Lucas, Eugene; Simmons, Okeefe; Tchang, Beverly; Aronne, Louis (Frontiers in Endocrinology, 2023)
While bariatric surgery results in significant long-term weight loss for most patients with obesity, post-surgical weight gain affects a considerable percentage of patients to varying degrees of severity. Furthermore, a small but significant percentage of patients experience inadequate post-surgical weight loss. Although many studies have examined the role of anti-obesity medications to address post-operative weight regain, an evidence-based consensus has not yet been achieved because of the heterogeneity of populations studied and the studies themselves. Observational studies in the post-bariatric surgery population consistently demonstrate the benefit of medical weight management after bariatric surgery, with most evidence highlighting liraglutide, topiramate, and phentermine/topiramate. New anti-obesity medications are anticipated to be helpful for post-surgical weight optimization given their efficacy in the non-surgical population.